2015
DOI: 10.1016/j.ijgo.2015.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Systematic reviews and meta-analyses of benefits and harms of cryotherapy, LEEP, and cold knife conization to treat cervical intraepithelial neoplasia

Abstract: Despite a comprehensive search, there is very low quality evidence and often no evidence for important outcomes, including reproductive outcomes and complications. Studies assessing these outcomes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(142 citation statements)
references
References 29 publications
4
114
1
6
Order By: Relevance
“…For this analysis, we reasonably assumed (approximated) that all CIN3/AIS was successfully treated, given the efficacy of excisional treatments to treat CIN3/AIS [22]. We also calculated diagnostic yield, precancers per 1,000 cotests or precancers and cancers per 1,000 cotests, as surrogate measure of programmatic efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…For this analysis, we reasonably assumed (approximated) that all CIN3/AIS was successfully treated, given the efficacy of excisional treatments to treat CIN3/AIS [22]. We also calculated diagnostic yield, precancers per 1,000 cotests or precancers and cancers per 1,000 cotests, as surrogate measure of programmatic efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…[46] Furthermore, a meta-analysis reported that 14.8% (65/439) of the women treated with cryotherapy had infertility and 12 reported spontaneous abortions in 210 pregnancies. [51] Scaling-up programs will require planners to keep in mind that if diagnostic services are provided at the screening site, fewer women would need to be referred, thereby reducing loss to follow-up. In waiting for diagnostic confirmation, this model also prevents overtreatment by cryotherapy, which has been reported in the ‘screen and treat’ model.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the pathological diagnosis was conducted as blindness by a single experienced pathologist at baseline and after the 6-month intervention. Previous studies have reported that compared with other treating methods (cryotherapy and cold knife conization), LEEP is the main treatment modality of CIN2/3 [12-13], and colposcopy and cervical biopsy are the accepted diagnostic tests of CIN [13]. …”
Section: Methodsmentioning
confidence: 99%